HUBUNGAN ANTARA HIPERKOLESTEROLEMIA DENGAN NYERI KEPALA TIPE TEGANG - Adi Puspowati, Herlina Suryawati, Dwi Pudjonarko (Neurona Majalah Kedokteran Neuro Sains, 2014)
INTRODUCTION TENSIONTYPE HEADACHE TTH HAS THE GREATEST PREVALENCE OF OVERALL HEADACHE ORIGINATED FROM INFREQUENTEPISODIC AND FREQUENT TO CHRONIC THE RESULT IS A CHRONIC CENTRAL SENSITIZATION INFLAMMATORY PROCESS THAT OCCURS IS AFFECTED BY THE MECHANISM OF NO NITRIC OXIDE THROUGH A HIGHCHOLESTEROL DIET